Optimizing selenium-enriched yeast supplementation in laying hens: Enhancing egg quality, selenium concentration in eggs, antioxidant defense, and liver health - Zhang, Longfei; Zhou, Jianmin; Obianwuna, Uchechukwu Edna; Long, Cheng; Qiu, Kai; Zhang, Haijun; Qi, Xiaolong; Wu, Shugeng (Poultry science, 2025)
This study evaluated the effects of selenium-enriched yeast (SY) supplementation at various levels on health and production parameters in laying hens, including egg production, egg quality, selenium (Se) concentrations in eggs, liver health, serum biochemical markers, antioxidant function, and immune responses. A total of 360 Hy-Line Brown hens (28 weeks old) were randomly assigned to four dietary groups with six replicates of 15 birds each, monitored over a 12-week feeding trial after a two-week acclimatization period. The dietary groups included a control (basal diet without selenium) and three SY-supplemented groups with Se levels of 0.3 mg/kg (SY03), 1.5 mg/kg (SY15), and 6.0 mg/kg (SY60). The results showed no significant effects of dietary SY on laying performance or feed efficiency (P > 0.05). However, the SY15 group showed significant improvements in egg quality, particularly in albumen height, Haugh Unit and yolk color (P < 0.05). Selenium concentrations in eggs, albumen, and yolk increased dose-dependently, with significant differences in the SY-supplemented groups (P < 0.001). Increased activities of liver enzymes including alanine transaminase, alkaline phosphatase, and aspartate transaminase, alongside elevated levels of uric acid were notable in the SY60 group (P < 0.05). In addition, histological analysis revealed significant hepatocyte degeneration and a higher liver organ index (P < 0.05), in the SY60 group. All of which suggests potential liver toxicity at higher selenium levels. Antioxidant capacity of the birds were significantly enhanced due to dietary supplementation of SY as indicated by increased serum levels of total antioxidant capacity, and activities of catalase, glutathione peroxidase, and superoxide dismutase (P < 0.05). Analysis of hepatic genes expression revealed that SY15 supplementation significantly upregulated key antioxidant-related genes (Nrf2, HO-1, CAT, and NQO1) and downregulated Keap1 expression (P < 0.05), suggesting strong activation of the antioxidant defense system. In conclusion, SY supplementation at 1.5 mg/kg improved egg quality, increased Se concentrations in eggs, and enhanced antioxidant capacity without affecting laying performance or liver health. This makes it a balanced approach to improving egg quality and poultry health. However, higher supplementation levels (6.0 mg/kg) resulted in liver damage, underscoring the importance of careful dosage consideration.